Risk Management Domain Application Plan Electronic Based Governance System (SPBE) Case Study: Tangerang Government Communications and Informatics Service - Ipung Sutejo, Bayu Sulistiyanto; Widodo, Agung Mulyo; Firmansyah, Gerry; Tjahjono, Budi (Jurnal Indonesia Sosial Sains, 2023)
Various applications of SPBE have been produced by the Central and Regional Authorities and have contributed to the efficiency and effectiveness of government maintenance. Nevertheless, the results of the SPBE development show a relatively low maturity rate and a high gap between the Central Authority and the Regional Government. Based on the results of the 2018 SPBE evaluation of 616 Central and Regional Government Instances, the National SPBE Index reached a value of 1.98 with a sufficient predicate of the target SPBE index of 2.6 out of 5 levels with a good prediction. Reviewed from the access of Central and Regional Authorities, the average Central Authorities SPBE index was 2.6 with a good predicate, while the average Regional Government SPBE Index was 1.87 with a sufficient Predicate. Reviewed from the target access spread, 13.3% of Central and Regional Authorities have reached or exceeded the target SPBE 2.6 index, while 86.7% have not yet reached the SPBE 2.0 index target. This shows that there are problems in the development of the SPBE nationally. On the other hand, the development of ICT 4.0 trends is a key external factor that can drive the realization of integrated SPBE implementation and improved quality of SPBE services that make it easier for users in accessing government services. The vision is a benchmark in implementing the integrated implementation of SPBE in the Central and Regional Authorities to produce integrative, dynamic, transparent, and innovative government bureaucracy, as well as improving the quality of integrated, effective, responsive, and adaptive public services.